2013
DOI: 10.1371/journal.pone.0059574
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Novel Functional Variant in the PPP2R1A Promoter on the Regulation of PP2A-Aalpha and the Risk of Hepatocellular Carcinoma

Abstract: Previously, we identified the genetic variant −241 (−/G) (rs11453459) in the PP2A-Aα gene (PPP2R1A) promoter and demonstrated that this variant influences the DNA-binding affinity of nuclear factor-kappa B (NF-κB). In this study, we further confirmed that the transcriptional activity of PPP2R1A may be regulated by NF-κB through the functional genetic variant −241 (−/G). Moreover, we also demonstrated that the methylation status of CpG islands in the promoter of PPP2R1A influences the activity of this gene prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Furthermore, PP2A activation shows a promising anti-tumor effect in breast cancer [ 25 ]. Our previous studies have shown that the genetic variant -241 (-/G) (rs11453459) in the 5’-flanking region of PPP2R1A contributes to the decreased risk of HCC in a southern Chinese Han population [ 26 ]. Moreover, other studies have demonstrated that the regulation of regulatory B subunits of PP2A (PP2A-Bs), such as B55β and B56γ, play important roles in cancer development or treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PP2A activation shows a promising anti-tumor effect in breast cancer [ 25 ]. Our previous studies have shown that the genetic variant -241 (-/G) (rs11453459) in the 5’-flanking region of PPP2R1A contributes to the decreased risk of HCC in a southern Chinese Han population [ 26 ]. Moreover, other studies have demonstrated that the regulation of regulatory B subunits of PP2A (PP2A-Bs), such as B55β and B56γ, play important roles in cancer development or treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the observed frequency of CAPs in our phosphatase interaction network is much higher than expected from a random network of similar size (p < 2.2 À16 ) ( Figure 7A, inset) and reveals many links to various forms of cancer. For example, the PP2A network harbors five CAPs including the PP2A regulatory subunit alpha (2AAA/PPP2R1A), which is also a CAP related to several carcinomas such as ovarian and hepatocellular carcinomas ( Figure 7A) (Chen et al, 2013;Rahman et al, 2013). The other four CAPs are lipoma-preferred partner (LPP), FGFR1 oncogene partner (FR1OP), CCDC6, and ZCHC8 ( Figure 7A).…”
Section: Protein Phosphatases and Human Cancermentioning
confidence: 99%
“…Similar studies have reported that the relation between gene polymorphism and cancer risk was more obvious in certain subgroup, which may result from different characteristic of the host (e.g. environmental factors and immune conditions) (Yang et al, 2011;He et al, 2012;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 54%